Birth Order Characteristics of the Penderwick Sisters in Jeanne Birdsall’s the Penderwicks Series - Sarah Nurul Anggreni; Rahmawan Jatmiko (Lexicon, 2022)
This research analyses the middle grade series, The Penderwicks, written by Jeanne Birdsall. The object of analysis of this research is the main characters of the series, The Penderwick sisters. The objective of this research is to analyse whether or not the characteristic that the Penderwick sisters possess fit into their designated birth order characteristic that was proposed by Alfred Adler. This research also uses Murtagh John Murphy’s theory of characterisation because this theory is the one that meets the requirement to analyse works using a close reading method. The result of this assessment shows that each Penderwick sister has very distinct characteristics. However, only some of the characteristics that the Penderwick sisters possess that fit into Adler’s birth order characteristics.